Improving Students Speaking Skills Through Local Storytelling - Pratiwi, Ajeng; Rahman Hz, Benni Ichsanda (Lembaran Ilmu Kependidikan, 2024)
This study is aimed to assess the efficacy of employing local storytelling to enhance the speaking skills of grade XII students in an English language classroom, involving 18 participants from a Pivate School in Medan. Utilizing the action research method, the study implemented two intervention cycles centered on local stories, namely "The Legend of Malin Kundang" and "The Origin of Lake Toba." Pre-tests and post-tests were administered to evaluate fluency, pronunciation, vocabulary, and grammar. Surprisingly, results indicated a decline in speaking scores across both cycles, falling short of the target score of 75. Despite attempts to engage students through storytelling, challenges like insufficient participation, attention, and confidence impeded the intervention's effectiveness. This highlights the need for supplementary strategies beyond storytelling to enhance speaking skills effectively. The findings contrast with prior research advocating for storytelling's efficacy in improving speaking skills, necessitating the exploration of alternative approaches such as interviews and group discussions. Acknowledging limitations, the study underscores the necessity for broader, more diverse research samples to generalize findings across educational contexts.